Occupational Correlation to the Level of Community Welfare Using The Apriori Algorithm (Case Study: Mangga Village) - Adlin Revaldi, Aulia; Novriyenni; Kadim, Lina Arliana Nur (Yayasan Kita Menulis, 2023)
Mango village is one of the areas that participates in various welfare programs for the local community, where in this village there are still people who are far from prosperous because of various factors that affect the welfare of the local community, one of which is the jobs owned by the community. Therefore, it is important for people to understand that work also greatly influences the level of welfare for their own lives, so that they are fulfilled in the economy, education and others. Therefore the author wants to create a system that can assist the government in developing community welfare programs in Mango Village by knowing the relationship between work and the level of social welfare. After carrying out the above case trials with minimum support = 25%, confidence = 100% so that the rule results that meet the support and confidence values are obtained, it can be concluded that if the assets owned are A4 (motorcycles), with T2 dependents (3-4), with M2 jobs (Private Employees) and A4 assets (Motorcycles), with P2 income (> 1,000,000 - < 2,000,000), then enter K2 (welfare stage II) with a support value of 20%, 100% confidence.